Stress and Simulated Environments: Insights From Physiological Marker - Liebherr, Magnus; Mueller, Silke M.; Schweig, Stephan; Maas, Niko; Schramm, Dieter; Brand, Matthias (Frontiers in Virtual Reality, 2021)
Driving in a simulator might induce stress, because of the confrontation with new environments, dealing with new technologies, as well as experience with symptoms of simulator sickness, which in turn may influence individuals’ driving performance. The present study aims to provide a better understanding of the association between simulated environments and humans’ stress level under consideration of age, simulator adaptation, experience with simulator sickness, and driving performance. Data from 164 participants (M = 61.62 years, SD = 12.66 years, ranging from 25 to 89 years, 42 women) were analyzed in the present study. During three measurement times, participants completed an advance first simulator drive (T0), followed by an online survey, assessing experience with simulator sickness (T1), and a second simulator drive (T2) including pre- and post-cortisol measurements. The hypothesized model shows no correlations of driving performance with experience with simulator sickness or stress level before and after a further simulator drive. Beyond the effect of age, previous experience with simulator sickness does further account for stress-level changes following a simulated drive but current driving performance did not. Despite the limitations and the partially contradictory results, the present study provides relevant findings for future simulator studies.